Pengaruh sanksi perpajakan, kesadaran wajib pajak dan pelayanan fiskus terhadap kepatuhan wajib pajak orang pribadi di kota Malang - Arista Genova Kaimuddin; Anggraeni Purwatiningsih (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2022)
This study aims to analyze the effect of tax sanctions on taxpayer compliance, analyze the effect of taxpayer awareness on taxpayer compliance, and analyze the effect of tax service services on taxpayer compliance. The sample in this study was 90 respondents. The analysis technique uses multiple regression analysis. The results of the analysis show that tax sanctions have an effect on individual taxpayer compliance. Taxpayer awareness has an effect on individual taxpayer compliance. Fiscal services have a significant effect on individual taxpayer compliance.